Diagnostic Accuracy of Diffusion Weighted MRI in Diagnosing Brain Abscess Taking Histopathology as Gold Standard - M. Haseeb Iqbal, Ummara Siddique Umer, Muhammad Salman Rafique, Abdullah Safi, Sana Kundi, Mahwish Jabeen, Aliya Sharif (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Diagnostic accuracy of DW-MRI in diagnosing brain abscess taking histopathology as gold standard. Methodology: A total of 407 patients having focal brain lesion on MRI of age 20-50 years of either gender were included. Patients with history of brain surgery, already established diagnosis on histopathology, claustrophobia and pregnant or breast feeding females were excluded. DW-MRI was done and conventional MRI sequences on 1.5 tesla MRI machine and presence or absence of brain abscess was noted. DW-MRI findings were correlated with histopathology. Results: Mean age was 38.53 ± 7.59 years. Out of these 407 patients, 262 (64.37%) were male and 145 (35.63%) were females with ratio of 1.8:1. Mean duration of disease was 4.87 ± 2.40 months. Mean size of lesion was 7.69 ± 4.52 mm. In DW-MRI positive patients, 221 were true positive and 32 were false positive. Among 154, DW-MRI negative patients, 18 were false negative whereas 136 were true negative (P-value=0.01). So in diagnosis of abscess in brain, sensitivity, specificity, PPV, NPV and DA of DW-MRI was 92.5%, 80.96%, 87.4%, 88.3% and 87.7% respectively. Conclusion: DW-MRI is the non-invasive modality of choice having high diagnostic accuracy (DA) i.. 87.7% in diagnosing brain abscess with sensitivity of 92.5% and specificity of 80.96%.